Microhistory, Hermeneutics, Statistics. On the Configuration of Memories in Krzysztof Zamorski’s Monograph Plebanus and the Village - Bugajewski, Maciej (Sensus Historiae, 2025)
Krzysztof Zamorski’s book Pleban i wieś [The Plebanus and the Village] is an original historical study of Polish society in early modern period, which, in terms of methodology, falls within the microhistorical writing tradition. In this article, I put forward two main theses. First, I attempt to show that the writing choices made by the author of the monograph mean that it not only brings the past of 18th-century Tenczynek closer to the reader, but also offers a discourse that can be interpreted as a contemporary configuration of a quasi-memory of the past. Second, I show that Zamorski’s narrative is a microhistorical approach based on previous research in historical demography. Grounding microhistory in historical demography makes Zamorski’s monograph an innovative achievement in contemporary historiography.